Idiopathic Pulmonary Fibrosis. Issue 3 (May 2016) - Martin, Maria D.; Chung, Jonathan H.; Kanne, Jeffrey P.
Abstract : Idiopathic pulmonary fibrosis (IPF) is the most common fibrosing lung disease and is associated with a very poor prognosis. IPF manifests histopathologically as usual interstitial pneumonia (UIP) and as subpleural and basal predominant reticulation with honeycombing on high-resolution computed tomography (HRCT) of the chest. When a high-confidence radiologic diagnosis of UIP is made on HRCT, surgical biopsy is rarely required. Therefore, radiologists should recognize a UIP pattern on HRCT as well as recognize other patterns of fibrosing lung disease such as nonspecific interstitial pneumonia or chronic hypersensitivity pneumonitis, both of which can be mistaken for UIP. This article reviews the clinical, CT, and histopathologic features of IPF, discusses the impact of CT findings on prognosis, and describes complications associated with IPF.